Chitosan as A Preservative for Fruits and Vegetables: A Review on Chemistry and Antimicrobial Properties - Chao Duan; Xin Meng; Jingru Meng; Md. Iqbal Hassan Khan; Lei Dai; Avik Khan; Xingye An; Junhua Zhang; Tanzina Huq; Yonghao Ni (Journal of Bioresources and Bioproducts, 2019)
Chitosan, derived from chitin, a major constituent (in quantity) of crustaceans, is a unique aminopolysaccharide with emerging commercial potential in agriculture, food, pharmaceuticals and nutraceuticals due to its nontoxic, biodegradable and biocompatable properties. Chitosan coating on fruits and vegetables has been found to be effective for the reduction of a variety of harmful micro-organims and extend the shelf-life of these products. In this review, our focus is on the antimicrobial properties of chitosan and its application as a natural preservative for fresh products. We detailed the key properties that are related to food preservation, the molecular mechanism of the antimicrobial activity of chitosan on fungi, gram-positive and gram-negative bacteria, coating methods for using chitosan and its formulation for preserving fruits and vegetables, as well as the radiation method of producing chitosan from chitin. Understanding the economic and scientific factors of chitosan’s production and efficiency as a preservative will open its practical application for fruits and vegetable preservation.